PANCASILA SEBAGAI DASAR PENGEMBANGAN ILMU PENGETAHUAN UNTUK KEMAJUAN BANGSA - Ritonga, Nur Nilam Sari (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This article aims to investigate how the values of Pancasila, including the values of the One Godhead, humanity, and social justice can serve as a moral framework that ensures that the development of science and technology not only focuses on technical achievements but also contributes to the welfare of the Community. This shows that Pancasila can serve as a solid foundation for the progress of science development in Indonesia, especially in the face of global problems such as materialism, limited access to technology and the influence of foreign cultures. Science that is morally responsible, inclusive, and just is driven by the principles of Pancasila, where Pancasila is able to ensure the development of knowledge that is relevant to the needs of society and still maintains the nation's identity.